Agreement between ultrasonography and histopatologic findings in diagnosing retinoblastoma - Fitria Natliani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Retinoblastoma is a rare eye tumor of childhood that represents the most common intraocular malignancy ofinfancy and childhood. Diagnosis of retinoblastoma are based on ophthalmological examination and imaging, includingultrasonography (USG). In a typical case of retinoblastoma, it will provide a nearly pathognomonic picture withcottage-cheese calcification, with density higher than the sclera and high internal reflectivity in USG findings.Histopathologic examination is a gold standard formalignany cases and Flexner-Wintersteiner cells is a pathognomonicsign. The aim of this study is to determine the value of an agreement test comparing USG as a preoperativediagnostic tool with histopatologic examination in diagnosing retinoblastoma. This study was an observationalagreement test. All of the patients with clinically suspected intraocular lession were examined with USG followedby surgery and histopathologic examination in Eye Clinic of Dr. Sardjito Hospital, Yogyakarta. The result of USGexaminationswas interpreted by one eye oncologist and the histopathologic readingwas performed by one anatomicalpathologist. Data were analyzed to determine the agreement value. Thirty three eyes, 21 eyes were retinoblastomasuspected and 12 eyes were non-retinoblastoma suspected based on USG examination), were observed in thisstudy. One eye (3.03%) was false positive case and 1 was false negative case. The Kappa value of agreement testwas 0.87. In conclusion, ultrasonography of the eye as a pre-operative diagnostic tool had an excellent agreementcompared with histopathological examination as a gold standard in retinoblastoma.Key words: eye-retina-intraocular malignancy-diagnosis-Kappa value